Relationship between perceived problem-solving skills and academic performance of novice learners in introductory programming courses - Ashok Kumar Veerasamy; Daryl D'Souza; Rolf Lindén; Mikko‐Jussi Laakso (Blackwell Publishing Ltd, 2022)
Past research has shown that student problem‐solving skills may be used to determine student final exam performance. This study reports on the relationship between student perceived problem‐solving skills and academic performance in introductory programming, in formative and summative programming assessment tasks. We found that the more effective problem solvers achieved better final exam scores. There was no significant difference in formative assessment performances between effective and poor problem solvers. It is also possible to categorize students on the basis of problem‐solving skills, in order to exploit opportunities to improve learning around constructivist learning theory. Finally, our study identified transferability skills and the study may be extended to identify the impact of problem solving transfer skills on student problem solving for programming.